Formulasi Sediaan Gel Basis Na-Cmc Ekstrak Etanol Daun Cocor Bebek (Kalanchoe Pinnata (Lmk.) Pers.) Sebagai Penyembuh Luka Bakar Pada Kelinci - Istiana, Sarah; , Tanti Azizah S, M.Sc.,Apt; , Suprapto, M.Sc., Apt (2016)
The compounds flavonoid, bufadienolides, saponin in the Kalanchoe pinnata have function to cure burns is the flavonoid. The mechanism of action flavonoid and bufadienolides as anti-bacterial with protein denature bacterial cell. Saponin mechanism by increasing collagen formation, so that wound be quickly healed. This study was aimed to determine the effectiveness of the ethanol extract of Kalanchoe pinnata gel to cure burns and to determine the concentration level of the ethanol extract of Kalanchoe pinnata gel to cure burn. The extraction of Kalanchoe pinnata was done by using ethanol 96% with maceration method. The rendemen result of Kalanchoe pinnata extract is 2,13%. The gel Na-CMC basis was made into 4 formulas, they are: gel without extract (F1), 1% gel (F2), 2.5% (F3) and 5% (F4). Gel evaluated the physical characteristic such as organoleptic, homogeneity, pH, viscosity, and dispersive power. The animal used for test were 6 Australian rabbits. The back skin of the rabbits was shaven then anaesthetized by using ethyl chloride spray, after that the inducers tool heated for 1 minutes was put on the skin for 5 second in a diameter of 2 cm. The result of the research showed that the ethanol extract of Kalanchoe pinnata gel did not have effect 0,332 (p> 0.05). Keywords: Kalanchoe pinnata, burns, Na-CMC